Longitudinal analysis of serological tests officially adopted by the Brazilian Ministry of Health for the diagnosis of canine visceral leishmaniasis in dogs vaccinated with Leishmune® - Marcondes, Mary [UNESP]; Lima, Valéria Marçal Felix de [UNESP]; de Araújo, Maria de Fátima Lereno; Hiramoto, Roberto Mitsuyoshi; Tolezano, José Eduardo; Vieira, Rafael F.C.; Biondo, Alexander W. (Elsevier, 2013)
Development of vaccines against canine visceral leishmaniasis (CVL) may provide a prophylactic barrier, but antibody response detected by standard diagnostic techniques may not separate vaccinated from naturally infected dogs. Moreover, anti-Leishmania antibody levels in vaccinated dogs may be detectable for months. Accordingly, the aim of the present study was to comparatively evaluate an in-house ELISA with three serological tests officially adopted by the Brazilian Ministry of Health for the diagnosis of CVL in dogs vaccinated with Leishmune®. A total of 18 mongrel dogs were submitted to a complete protocol of the vaccine, monitored and evaluated in 5 times (T0-T4) up to 180 days after T0. Twenty-one days after the first dose (T1), 50% of the dogs were seropositive by the in-house ELISA and 5.5% by IFAT, while by the official ELISA and DPP® CVL rapid test all dogs tested negative. At time T2, 42 days after of the first dose, 100%, 83.3%, 11.1%, and 5.5% of the dogs were seropositive by the in-house ELISA, IFAT, official ELISA kit and the DPP® CVL rapid test, respectively. Ninety days after the first dose (T3), 100%, 83.3%, 72.2% and 33.3% of the dogs were seropositive by the in-house ELISA, official ELISA kit, IFAT, and the DPP® CVL rapid test, respectively. Finally, at time T4, 88.8%, 33.3%, 11.1% and 5.5% of the dogs were seropositive by the in-house ELISA, official ELISA kit, DPP® CVL rapid test and IFAT, respectively. In conclusion, dogs vaccinated with Leishmune® cross-react by an in-house ELISA and by the three official Brazilian serological tests for the diagnosis of canine visceral leishmaniasis up to six months after the first vaccine dose, and may be mistakenly diagnosed and removed. © 2013 Elsevier B.V.
Keywords: DPP® CVL rapid test; ELISA; IFAT; Leishmania infantum